Sistemas de controle de vendas no setor têxtil: um estudo exploratório - Campos, Marcelo (2008)
This dissertation studies the sales control systems practiced by the Brazilian textile industry in face of the environmental changes of the last two decades. Such transformations reveal the strategic role of sales professionals, turning them into the main link between organizations and the set of purchasers. The basic premise for using sales team control systems is that by doing so one can manage and influence employees’ attitude and behavior in order to achieve objectives, with a close relationship between the way commercial management monitors, manages, assesses and rewards the activities of their salespeople and the effectiveness of the commercial area, which are decisive differentials to comply with the pressure for competitiveness and with market demands regarding the positioning of the commercial team in face of the new business context. Different studies have been carried out on sales controls in theory, covering economic, organizational and behavioral aspects, but none of them was specifically related to Brazil and to the textile industry, which has characteristics of its own that create opportunities for making the commercial control more complete. In the theoretical review the eight main control system models were identified as well as important aspects that should be taken into consideration in order to set up a system for each company. A survey was carried out with people in charge of sales teams in the textile sector in the segments where industrial sales are undertaken. Empirical techniques were used to identify the rate of occurrence of those aspects being studied, and it was found that the segments of fibers and filaments, spinning, weaving, knitting and finishing in the textile chain have relevant control systems with the characteristics of industrial sales. Formal controls are connected to results and informal controls are related to the follow-up of activities and salespeople’s skills. Furthermore, the view of people in charge of commercial teams regarding their effectiveness in aspects such as sales volume, profitability, market share, as well as customer satisfaction was determined. Conclusions include results and theoretical implications, limitations and suggestions for future work.